In our first equation, we can notice:
![(x^m*x^2)=x^{2+m}](https://tex.z-dn.net/?f=%20%28x%5Em%2Ax%5E2%29%3Dx%5E%7B2%2Bm%7D%20)
and
![(x^{m+2})^3*k^{15}=x^{21} *k^{15} \implies \\ x^{m+2}=x^{21}](https://tex.z-dn.net/?f=%20%28x%5E%7Bm%2B2%7D%29%5E3%2Ak%5E%7B15%7D%3Dx%5E%7B21%7D%20%2Ak%5E%7B15%7D%20%5Cimplies%20%5C%5C%20x%5E%7Bm%2B2%7D%3Dx%5E%7B21%7D%20)
So, using the fact that
, we have:
![m+2=21 \implies\\ m=19](https://tex.z-dn.net/?f=%20m%2B2%3D21%20%5Cimplies%5C%5C%20m%3D19%20)
In our second equation, we have:
![(x^3*y^2)(\frac{x^2y^3*z^m}{z^{-5}})=x^5y^5z](https://tex.z-dn.net/?f=%20%28x%5E3%2Ay%5E2%29%28%5Cfrac%7Bx%5E2y%5E3%2Az%5Em%7D%7Bz%5E%7B-5%7D%7D%29%3Dx%5E5y%5E5z%20)
So, using the exponent rules, we get:
![(x^3*y^2)(\frac{x^2y^3*z^m}{z^{-5}})=\\ x^{2+3}*y^{3+2}*z^{m-(-5)}=\\x^5*y^5*z^{m+5}](https://tex.z-dn.net/?f=%20%20%28x%5E3%2Ay%5E2%29%28%5Cfrac%7Bx%5E2y%5E3%2Az%5Em%7D%7Bz%5E%7B-5%7D%7D%29%3D%5C%5C%20x%5E%7B2%2B3%7D%2Ay%5E%7B3%2B2%7D%2Az%5E%7Bm-%28-5%29%7D%3D%5C%5Cx%5E5%2Ay%5E5%2Az%5E%7Bm%2B5%7D%20)
So, we can cross out the common factors in each to give us:
![z^{m+5}=z \implies\\ z^{m+5}=z^1 \implies \\ m+5=1 \implies \\ m=-4](https://tex.z-dn.net/?f=%20z%5E%7Bm%2B5%7D%3Dz%20%5Cimplies%5C%5C%20z%5E%7Bm%2B5%7D%3Dz%5E1%20%5Cimplies%20%5C%5C%20m%2B5%3D1%20%5Cimplies%20%5C%5C%20m%3D-4%20)
So, using the exponent rules, we found the m values in both equations.